Personal taxation in Nigeria : including capital gains tax and capital transfer tax - Ariwodọla, J. A. (Lagos : JAA Nigeria Ltd., 1993)
The book is intended to assist student undertaking courses in taxation. It covers all the ramification of personal tax. He explains all the principles within the context of the law leads the reader to series of examples using the Nigerian experiences and materials.
Includes index.
gp. 24/01/2019, ijb 27/03/2019
Loans
Keywords: Personal taxation; Capital gains tax; Income tax; Capital transfer tax; Nigeria